Case report of optimizer implantation to modulate cardiac contractility in patients with chronic heart failure and atrial fibrillation - Pushkareva AE; Blagodarov SI; Abdrakhmanov RE; Plotnikova MR; Dolganov AA; Mustafina IA; Zagidullin NSh (Archives of Clinical Hypertension - Peertechz Publications, 2023)
A cardiac contractility modulation device is a new treatment used in patients with heart failure. CCM therapy is associated with an increase in physical activity tolerance, improved quality of life, reduced hospitalizations due to heart failure, and reverse remodeling of the left ventricle in patients with systolic heart failure. In this case, the clinical benefit of cardiac contractility modulation in a patient with chronic heart failure, atrial fibrillation and postinfarction left ventricle aneurysm was reported. Development of postinfarction left ventricle aneurysm in patients with reduced ejection fraction is associated with a high risk of surgical complications. However, an adequate assessment of the functional reserve of the left ventricle myocardium and the choice of surgical correction method allows for receiving favorable outcomes of surgery. We present a case of a successful combination of interventional and surgical treatment of a patient with heart failure and post-infarction left ventricular aneurysm.